Demand-driven forecasting: sensing, shaping, and predicting demand - Chase, Charlie (Henry Stewart Talks, 2010)
Improvements in demand-driven forecasting, Problems companies face, What is demand-driven forecasting?, Role of sales and marketing, Domain knowledge vs. judgement, Role of the finance department, Consensus forecasting sub-process and process, Business intelligence (BI) portals/dashboards, Importance of BI tools/application, Demand-driven forecasting process flow model, Benefits of demand-driven forecasting, Demand forecasting enabling technology requirements, A good demand-driven forecasting process and steps to improve yours, Conclusions, References